ANALISIS FAKTOR-FAKTOR KEBERHASILAN ELEKTRONIK GOVERNMENT PADA PEMERINTAH KABUPATEN JEPARA - Khoirul Anwar; Titik Djumiarti; Rihandoyo Rihandoyo (Journal of Public Policy and Management Review, 2013)
The use of information and communication technologies very important in the globalization area. Based on the presidential intruction No. 3 of 2003 on local governments to take advantage of information technology white the avilable resources with in thegovernmental activities, including the district of jepara. The use of IT will give birth to an electronic-based system of government (e-Government). Thesuccessful implementation of e-Government is very influentialon the efficiency, effectiveness, seen from the successful elements of the Harvard JFK School of Government are Support, Capacity and Value.This research aims to determine the implementation of e-Government of Jepara and determie the factors that drive and inhibit. Attempt to answer the problems and research objective successfully done white parliaments of Harvard JFK School of Government. Methodology used in this research is qualitative diskripsif.Successful of implementation of the elements of e-Government in Jepara, are; website creation www.jeparakab.go.id, the increasing of infrastructure development the private sectors and do learning improvement one-Government. The success rate ofimplementation of e-Government in Jepara regencyin on their level of maturation.In the development of e-Government it is necessary to support program of e- Government, the need for cooperation on increase the budget, the need for socialization of the exstence of e-Government directly from the government and the use of information tecnology.